2016
DOI: 10.1166/jbn.2016.2216
|View full text |Cite
|
Sign up to set email alerts
|

Folate-Modified Chitosan Nanoparticles Coated Interferon-Inducible Protein-10 Gene Enhance Cytotoxic T Lymphocytes' Responses to Hepatocellular Carcinoma

Abstract: Adoptive therapy using tumor antigen-specific cytotoxic T lymphocytes (CTLs) is a promising approach for treatment of human cancers. Due to immune suppression in cancer patients, it is difficult for tumor antigen-specific CTLs to arrive at tumor tissues. Interferon-inducible protein-10 (IP-10) is a powerful chemokine that effectively attracts CTLs to tumor tissues and improves their anti-tumor activity. Increase over expression of IP-10 in tumor tissues can efficiently promote efficacy of adoptive therapy. Fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…In addition, chitosan possesses good adhesion to the stromal cells; this is important for the design of the scaffolds [4,15,16]. Chitosan derivatives are used as hydrogels or nanoparticles for the design of the carriers of drugs, the agents for diagnostics of food additives or cancer, as well as for the design of materials for the extraction of toxic heavy metals from wastewaters [17][18][19][20][21][22]. The functional groups of chitosan, especially the amino groups, give an opportunity of the chemical functionalization of this aminopolysaccharide; this permits one to extent a range of the materials on base of chitosan as well as improving characteristic properties of them.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, chitosan possesses good adhesion to the stromal cells; this is important for the design of the scaffolds [4,15,16]. Chitosan derivatives are used as hydrogels or nanoparticles for the design of the carriers of drugs, the agents for diagnostics of food additives or cancer, as well as for the design of materials for the extraction of toxic heavy metals from wastewaters [17][18][19][20][21][22]. The functional groups of chitosan, especially the amino groups, give an opportunity of the chemical functionalization of this aminopolysaccharide; this permits one to extent a range of the materials on base of chitosan as well as improving characteristic properties of them.…”
Section: Introductionmentioning
confidence: 99%
“…After intravenous injection of GX1-DGC-DCT, tumour growth in xenograft gastric cancer models showed a tumour inhibition rate of 67.05% compared with the single DCT group (145). Some similar studies in gastric cancer reported that chitosan oligosaccharide (COS)-conjugated selenium (Se) and carboxymethyl chitosan (CMCS)-conjugated norcantharidin (NCTD) could remarkably enhance its antitumour efficacy (153)(154)(155)(156). PEG, polylactic acid (PLA), and polycaprolactone (PCL) are FDA-approved commercially available biodegradable copolymers that are widely used to prepare nanoparticles for drug delivery (157).…”
Section: Polymeric Nanoparticles and Liposomesmentioning
confidence: 99%
“…In cancer, chitosan is mainly used in chemotherapeutic delivery and as an immunoadjuvant in vaccines (102). Folate (FA)-modified chitosan has demonstrated to enhance tumor targeting and cytotoxic T-cell responses in some oncological settings (103)(104)(105)(106). FA-modified chitosan nanoparticles carrying a plasmid of the mouse interferon-induced protein-10 (mIP-10) gene, a chemoattractant for cytotoxic T cells, reduced MDSCs from spleen, tumor, and bone marrow in combination with a DC/tumor cell fusion vaccine in hepatocellular carcinomabearing mice (67).…”
Section: Other Combinatorial Treatmentsmentioning
confidence: 99%